Karyosystematic Studies in Amorphophallus Blume ex Decne. - Anil, Shirly Raichal; S, Suhara Beevy; EA, Siril (JOURNAL OF ROOT CROPS, 2015)
Cytological studies in 25 accessions revealed the occurrence of three chromosome numbers viz., 2n=28 for all the Amorphophallus paeoniifolius accessions, A. dubius, A. smithsonianus and A. sylvaticus; 2n=26 for A. bonaccordensis, A. hohenackeri and A. commutatus; and 2n=3x=39 for A. bulbifer. Zarco’s asymmetry indices revealed that the accessions T2 (A. bonaccordensis) and T3 (A. smithsonianus) were the more evolved species in terms of karyotype symmetry. According to the classification of Stebbins, A. bonaccordensis included in 3B category was the most asymmetrical and hence considered as most evolved. Amorphophallus paeoniifolius var. campanulatus with A1=0.40-0.43 appeared to be more evolved than A. paeoniifolius var. paeoniifolius based on Zarco’s asymmetry indices. Slight differences observed in the A1 values (0.1714-0.37) in the accessions of A. paeoniifolius var. paeoniifolius demonstrated the close relationship of the accessions. Taxa with asymmetric karyotype tend to have low total form (TF)% and accordingly cv. Gajendra (GJ) and cv. Karunaikizhangu (T10) (both classified as A. paeoniifolius var. campanulatus) having low TF% can be considered as highly evolved among the A. paeoniifolius accessions. UPGMA clustering based on five karyotypic parameters namely total chromosome length (TCL), average chromosome length (ACL), chromosome number, TF% and ratio of longest chromosome (LC) to shortest chromosome (SC) of the complement revealed two principal clusters at a Euclidean distance of 1.3. The two cultivars of A. paeoniifolius var. campanulatus (GJ and T10) along with A. dubius (A.d) were clustered in a single sub-cluster. Such clustering pattern is in tune with the morphological data which leads to make a valid assumption that A. dubius is a possible ancestor of the cultivars GJ and T10.